НАРОДНЕМИСТЕЦТВО ЯК ЗАСІБ ЕТНОКУЛЬТУРНОЇ ІДЕНТИФІКАЦІЇ ОСОБИСТОСТІ - Мохірєва, Юлія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті автор пропонує вирішення однієї з актуальних проблем сучасної мистецької освіти – формування справжнього митця-громадянина з глибоким відчуттям культурно-родинної ідентичності, яке можливе на основі національної духовності через засвоєння принципів і форм народної культури, зокрема художньої спадщини. Запорукою успіху є: звернення майбутніх учителів образотворчого мистецтва до етнічної традиції, пошук нових інноваційних форм вираження, високий професійний рівень. В статье автор предлагает решение одной из актуальных проблем современного изобразительного образования – формирование настоящего художника-гражданина с глубоким чувством культурно-семейной идентичности, которое возможно на основе национальной духовности через усвоение принципов и форм народной культуры, в частности, художественного наследия. Для успешного решения проблемы необходимо: обращение будущих учителей изобразительного искусства к этнической традиции, поиск новых инновационных форм выражения, высокий профессиональный уровень. In research autors propounds determination one of topical problems of modern art education - forming a true artist-citizen with feeling of familycultural identity, which are possible on basis of national spirituality owing to assimilation principles and forms of national culture. The garanty of success are: appeal to future teachers of descriptive art to ethnic traditions, searching for the new innovative forms of expression, high professional level degree. Now is disclosed pedagogical-cultural potential of learning art of modern Ukrainian artists, and, in particular, of art dynasty of Poltava. In the chail of art Poltava’s national pedagogical university named be V. Korolenko theoretical knowledge about history of Ukrainian art, it’s modern condition, supported by deep personal informative processes. Great attention is givet to mastery of students practical skills. Conceptualizing source of Ukrainian art like the most important spiritual factor; students are teaching an art techiques of expression: they are developing compositions degree of difficulty; using computer techologies; young artists are joining to art exhibition.